Discovery of nonpeptide 3, 4-dihydroquinazoline-4-carboxamides as potent and selective sst2 agonists. Issue 17 (1st September 2020) - Zhao, Jian; Wang, Shimiao; Han, Sangdon; Kim, Sun Hee; Kusnetzow, Ana Karin; Nguyen, Julie; Rico-Bautista, Elizabeth; Tan, Hannah; Betz, Stephen F.; Scott Struthers, R.; Zhu, Yunfei
Graphical abstract: Abstract: Nonpeptide sst2 agonists can provide a new treatment option for patients with acromegaly, carcinoid tumors, and neuroendocrine tumors. Our medicinal chemistry efforts have led to the discovery of novel 3, 4-dihydroquinazoline-4-carboxamides as sst2 agonists. This class of molecules exhibits excellent human sst2 potency and selectivity against sst1, sst3, sst4 and sst5 receptors. Leading compound 3-(3-chloro-5-methylphenyl)-6-(3-fluoro-2-hydroxyphenyl)-N, 7-dimethyl-N-[(2S)-pyrrolidin-2-yl]methyl-3, 4-dihydroquinazoline-4-carboxamide (28 ) showed no inhibition of major CYP450 enzymes (2C9, 2C19, 2D6 and 3A4) and weak inhibition of the hERG channel.